Living within the safe and just Earth system boundaries for blue water - Stewart-Koster, Ben; Bunn, Stuart E.; Green, Pamela; Ndehedehe, Christopher; Andersen, Lauren S.; Armstrong McKay, David I.; Bai, Xuemei; Declerck, Fabrice; Ebi, Kristie L.; Gordon, Christopher; Gupta, Joyeeta; Hasan, Syezlin; et al. (Nature Portfolio, 2024)
Safe and just Earth System Boundaries (ESBs) for surface water and groundwater (blue water) have been defined for sustainable water management in the Anthropocene. Here we assessed whether minimum human needs could be met with surface water from within individual river basins alone and, where this is not possible, quantified how much groundwater would be required. Approximately 2.6 billion people live in river basins where groundwater is needed because they are already outside the surface water ESB or have insufficient surface water to meet human needs and the ESB. Approximately 1.4 billion people live in river basins where demand-side transformations would be required as they either exceed the surface water ESB or face a decline in groundwater recharge and cannot meet minimum needs within the ESB. A further 1.5 billion people live in river basins outside the ESB, with insufficient surface water to meet minimum needs, requiring both supply- and demand-side transformations. These results highlight the challenges and opportunities of meeting even basic human access needs to water and protecting aquatic ecosystems.